Hybrid Legality in Imported Thrifting: Navigating the Intersection of Fiqh Muamalah and State Regulatory Authority in Contemporary Indonesia - Adam Malik; Rara Mila Hafidzoh; Reva Aulia; Muhammad Sayuti Hasan (NALAR FIQH: Jurnal Hukum Islam, 2026)
The rapid expansion of transnational second-hand clothing markets, commonly known as imported thrifting, has generated significant legal controversy in Indonesia, where the government formally prohibited the importation of used clothing through Ministerial Regulation of Trade Number 40 of 2022. This regulatory prohibition creates a complex normative tension, as imported thrifting transactions appear, on their face, to satisfy the contractual pillars and conditions of validity under Islamic commercial jurisprudence (fiqh muamalah), yet are simultaneously subject to state prohibition on grounds of public health protection, domestic industry preservation, and macroeconomic stability. Existing scholarship has addressed these dimensions in isolation, leaving a significant theoretical gap in understanding how Islamic commercial law and state regulatory authority interact within the same economic phenomenon. This study addresses that gap through a normative legal research design employing comparative-normative analysis across three sequential analytical stages: internal assessment of transactional validity under fiqh muamalah, examination of the policy rationale of Indonesian positive law, and dialectical synthesis through the maqasid al-shariah framework. The findings establish that imported thrifting operates simultaneously within two non-contradictory normative registers, private validity under Islamic contract law and public prohibition under state regulation, a condition this study terms "hybrid legality." The analysis further demonstrates that the state's regulatory prohibition carries robust Islamic normative legitimacy through the objectives of hifz al-nafs and hifz al-mal at the collective level, and through the jurisprudential principle of tasarruf al-imam 'ala al-ra'iyyah manut bi al-maslahah. The concept of hybrid legality is proposed as an original analytical model for understanding transnational economic phenomena in contemporary Muslim societies, offering a framework that transcends the binary halal-haram dichotomy and situates Islamic legal reasoning within broader debates on legal pluralism, state authority, and public welfare governance.